Noninvasive cardiac assessment in children of women with systemic lupus erythematosus - Leite,Maria de Fátima Monteitro Pereira (2003)
OBJECTIVE: Noninvasive cardiac assessment of newborns and infants of women with systemic lupus erythematosus. The children had no congenital total atrioventricular block and were compared with the children of healthy women. METHODS: We prospectively assessed 13 newborns and infants aged 1 to 60 days, children of women with systemic lupus erythematosus and without congenital total atrioventricular block. These children were compared with 30 children of women who had no lupus or anti-Ro/SSA antibodies, and no risk factors for congenital heart disease either. Their age groups matched. The following examinations were performed: cardiological physical examination, electrocardiography, echocardiography, and signal-averaged electrocardiography. RESULTS: The statistical analysis showed no significant difference in ventricular function or in the cardiac conduction system between the groups. CONCLUSION: In regard to the conduction system and ventricular function in the absence of total atrioventricular block, no statistically significant difference was observed between the children of women with systemic lupus erythematosus and children of healthy women.